Industrial energy efficiency potentials: an assessment of three different robot concepts. Issue 3 (4th May 2017) - Kurilova-Palisaitiene, J.; Permin, E.; Mannheim, T.; Buhse, K.; Lorenz, M.; Schmitt, R.; Corves, B.; Björkman, M.
Abstract: The rise in energy consumption and the associated costs instigate financial concerns among industrial energy consumers. For industrial processes addressing heating and cooling as well as material transformation, a wide range of energy efficiency measures have been developed and successfully implemented. In contrast to that, most robot-based operations such as pick-and-place motions or assembly tasks still use inefficient standard concepts causing high-energy consumption and high-energy costs. Thanks to a rather low payload-to-weight ratio of new robot designs, such as parallel kinematic or hybrid robot manipulators, a high potential for energy savings is expected. This article identifies potentials for energy saving concerning industrial consumers by assessing three different robot concepts. Based on a literature review, two existing designs for robots – the conventional serial robot and the parallel kinematic robot are analysed and compared with respect to the energy utilised during a typical item placement task. Afterwards, the concept of PARAGRIP, a hybrid of the two presented robot designs is introduced and examined based on simulation regarding its energy consumption. The final results demonstrate significantly different energy consumptions between the robot concepts, identifying potential savings of about 40% in a selected industrial application scenario.